Superconvergence of finite volume methods for the second order elliptic problem - Chou, So-Hsiang; Ye, Xiu (Computer methods in applied mechanics and engineering, 2007)
This paper derives a superconvergence result for finite volume approximations of the second order elliptic problem by using a L 2 projection post-processing technique. The superconvergence result is applicable to different kind of finite volume methods and to general quasi-uniform meshes.